Chilli thrips Scirtothrips dorsalis Hood (Insecta: Thysanoptera: Thripidae) - Vivek Kumar Jha; Dakshina R. Seal; Garima Kakkar (EDIS, 2010)
Revised! EENY463, an 11-page fact sheet by Vivek Kumar Jha, Dakshina R. Seal, and Garima Kakkar, is part of the Featured Creatures collection. It describes this new introduced insect pest that is an important pest of vegetable, ornamental, and fruit crops — synonymy, distribution, identification, life cycle and biology, hosts, damage, disease transmission, management. Includes references. Published by the UF Department of Entomology and Nematology, October 2009. Revised January and August, 2010.